Calcular derivada

Calcula la derivada de las funciones:

- y = x^3 \cdot e^x
- y = x^3 \cdot 3^{x^2}

SOLUCIÓN

- y = x^3 \cdot e^x

Usaremos la fórmula de la derivada de un producto

(u \cdot v)' = u' \cdot v + u \cdot v'

Para nuestro ejemplo sería:

y = \underbrace{x^3}_{u} \cdot \underbrace{e^x}_{v}

Entonces:

y' = 3x^2 \cdot e^x + x^3 \cdot e^x

Simplificando tendríamos:

y' = (3x^2 + x^3) \cdot e^x

- y = x^3 \cdot 3^{x^2}
Usaremos la fórmula de la derivada de un producto

(u \cdot v)' = u' \cdot v + u \cdot v'

Para nuestro ejemplo sería:

y = \underbrace{x^3}_{u} \cdot \underbrace{3^{x^2}}_{v}

Entonces:

y' = 3x^2 \cdot 3^{x^2} + x^3 \cdot 3^{x^2} \cdot 2x \cdot Ln(3)